2009
DOI: 10.1088/0741-3335/51/4/044005
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental ion cyclotron resonance heating of JET deuterium plasmas

Abstract: Radio frequency heating of majority ions is of prime importance for understanding the basic role of auxiliary heating in the activated D-T phase of ITER. Majority Deuterium Ion-Cyclotron Resonance Heating (ICRH) experiments at the fundamental cyclotron frequency were performed in JET. In spite of the poor antenna coupling at the lowest possible commissioned RF frequency (25MHz), this heating scheme proved promising when adopted in combination with D Neutral Beam Injection (NBI). The experiments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…It has been experimentally observed that simultaneously applying NBI and IRCH heating simultaneously results in more heating than the sum of either of them alone [18]. Our results provide a possible explanation for this phenomenon.…”
Section: Discussionsupporting
confidence: 61%
“…It has been experimentally observed that simultaneously applying NBI and IRCH heating simultaneously results in more heating than the sum of either of them alone [18]. Our results provide a possible explanation for this phenomenon.…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, D and 4 He ions have the same (Z/A) = 1/2 and thus there is no MC layer in the plasma and no local amplification of the E + field. In fact, pulse #55714 is very similar to the discharges studied in [10,11], and highlights that fundamental ICRH heating of beam ions can be made significantly much more efficient in plasmas with a purposely chosen particle composition. [14]).…”
Section: Resultsmentioning
confidence: 67%
“…Note that the Doppler-shifted ion cyclotron absorption by D-beam ions in D plasmas was earlier reported on JET [10,11]. In those experiments there was no MC layer present in the plasma, and the double-pass absorption was computed to be 5-15% [11].…”
Section: Introductionmentioning
confidence: 57%
“…One of the most interesting applications of the CNS to ASDEX Upgrade plasmas is the investigation of the synergy effect between NBI and the Ion Cyclotron Resonance Heating [13,14]. It is a common observation in tokamaks that adding radio-frequency heating on top of NBI enhances the neutron rate by more than the rate associated with ICRH only under the same experimental conditions and plasma parameters [15]. An example for an ASDEX Upgrade discharge is shown in figure 8.…”
Section: Jinst 7 C03004mentioning
confidence: 99%